Haemostatic profile of reconstituted blood in a proposed 1:1:1 ratio of packed red blood cells, platelet concentrate and four different plasma preparations. (May 2015) - Ponschab, M.; Schöchl, H.; Gabriel, C.; Süssner, S.; Cadamuro, J.; Haschke‐Becher, E.; Gratz, J.; Zipperle, J.; Redl, H.; Schlimp, C. J.
Summary The concept of haemostatic resuscitation implies early and high‐volume plasma transfusion. We investigated the haemostatic profile of reconstituted whole blood prepared in a 1:1:1 ratio of blood, platelets and plasma. This consisted of packed red blood cells, platelet concentrate and four different plasma variants: fresh frozen; solvent‐detergent; lyophilised quarantine; and lyophilised methylene blue‐inactivated plasma. Haematocrit, platelet count, endogenous thrombin potential and coagulation factor activity were significantly lower in reconstituted blood compared with citrated whole blood (p < 0.01). Except for lyophilised methylene blue‐inactivated plasma, no substantial differences between plasma variants in coagulation factor activity, endogenous thrombin potential and standard coagulation tests were observed. After reconstitution, haematocrit and platelet counts were slightly above recommended transfusion triggers, most thromboelastometry (ROTEM®) parameters were within the normal range and fibrinogen concentrations were between 1.57 g.l−1 and 1.91 g.l−1. Reconstitution of whole blood in a 1:1:1 ratio resulted in significant dilution of haematocrit and platelet count, but values remained above limits recommended by transfusion guidelines. Fibrinogen concentrations of reconstituted whole blood were also significantly reduced, and these were below the threshold value for supplementation recommended by recent guidelines.